1987
DOI: 10.1161/01.cir.76.6.1364
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of coronary atherosclerosis by propranolol in behaviorally predisposed monkeys fed an atherogenic diet.

Abstract: We studied the effect of propranolol on the diet-induced coronary artery atherosclerosis (CAA) in 30 adult male cynomolgus monkeys living in social groupings of five animals each. Animals in the "treated" segment (n = 15) consumed propranolol, which was mixed into an atherogenic diet. Animals in the "untreated" group (n = 15) consumed only the atherogenic diet. Finally, the social groupings were subjected to disruption through monthly redistribution of monkeys among the groups within each treatment segment. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
151
0
3

Year Published

1991
1991
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(159 citation statements)
references
References 35 publications
5
151
0
3
Order By: Relevance
“…Here we present an adrenergic signaling pathway that explains the rapid increase in activation of the transcription factor NF-B observed in PBMC shortly after exposure to psychosocial stress, thus linking psychosocial stress to mononuclear cell activation and subsequent changes in the immune system. This extends previous work showing a role of catecholamines in the mechanism for atherosclerosis (8)(9)(10)(11)(12). The observation that mental stress in humans and rodents results in nuclear translocation of NF-B and changes in transcriptional activity thus closes an important gap in understanding the cellular consequences of psychosocial stress.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Here we present an adrenergic signaling pathway that explains the rapid increase in activation of the transcription factor NF-B observed in PBMC shortly after exposure to psychosocial stress, thus linking psychosocial stress to mononuclear cell activation and subsequent changes in the immune system. This extends previous work showing a role of catecholamines in the mechanism for atherosclerosis (8)(9)(10)(11)(12). The observation that mental stress in humans and rodents results in nuclear translocation of NF-B and changes in transcriptional activity thus closes an important gap in understanding the cellular consequences of psychosocial stress.…”
Section: Discussionsupporting
confidence: 85%
“…Potential toxic elements in the personality construct such as hostility, anger, cynicism, mistrust, and unhealthy lifestyle (1,5,6), as well as social isolation (5), lack of social support (6), and work-related stress (7), increase the risk for cardiovascular disease, suggesting a strong causal relationship between chronic stress and the development of atherosclerosis (1). Intervention studies in cynomolgus monkeys support this concept, showing not only activation of these processes by mental stress but also reduction of vascular dysfunction and disease by reducing psychosocial stress through ␤-adrenergic blockade (8)(9)(10)(11)(12). Consistently, behavioral interventions, stress reduction, and stress management demonstrated benefits over and above usual medical care in hypertensive African Americans (13) and in cardiac patients with evidence of myocardial ischemia (14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…31 Further, heart rate is known to be a marker of sympathetic activity, and the oestrogen-induced changes in the present study were present when mean heart was elevated. 32 Our data may indicate an effect of oestrogen on vasodilatation via the sympathetic system. When HR is maintained on a higher level the difference in BP is present, but during the night-time, when the sympathetic system is less activated, the effect of oestrogen will not be so large.…”
Section: Discussionmentioning
confidence: 61%
“…These psychosocial factors are composed of depression, anxiety, personality and character traits as well as chronic and subacute life stress. 4,[10][11][12][13] A growing number of epidemiologic studies has suggested that anger and hostility are related to incidence of MI, 14 especially in older men. 14,15 Efforts to raise public awareness of these issues may carry a larger importance as terrorism remains a constant threat.…”
Section: Discussionmentioning
confidence: 99%